2017
DOI: 10.3390/s17071591
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Vicon System Positioning Performance

Abstract: Motion capture setups are used in numerous fields. Studies based on motion capture data can be found in biomechanical, sport or animal science. Clinical science studies include gait analysis as well as balance, posture and motor control. Robotic applications encompass object tracking. Today’s life applications includes entertainment or augmented reality. Still, few studies investigate the positioning performance of motion capture setups. In this paper, we study the positioning performance of one player in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
207
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 333 publications
(226 citation statements)
references
References 13 publications
2
207
1
2
Order By: Relevance
“…The preparation phase was necessary to ensure the integrity of the marker trajectories and force plate analog channels, and to limit the impact of manual errors that may have propagated through the original data capture pipeline [35,42]. First, the data mining relied on trials with the eight required marker trajectories being contiguous and labeled, together with associated KJM, and force plate channel data present throughout the entire stance phase.…”
Section: Data Preparationmentioning
confidence: 99%
“…The preparation phase was necessary to ensure the integrity of the marker trajectories and force plate analog channels, and to limit the impact of manual errors that may have propagated through the original data capture pipeline [35,42]. First, the data mining relied on trials with the eight required marker trajectories being contiguous and labeled, together with associated KJM, and force plate channel data present throughout the entire stance phase.…”
Section: Data Preparationmentioning
confidence: 99%
“…Within the test bed, localization of the robots is given by the Vicon motion tracking system (Vicon motion systems Inc., Oxford, United Kingdom) with millimeter precision. In the study done by Merriaux et al, 34 it has been proven that the Vicon system can achieve errors below 2 mm at common speeds, and below 1 mm for static objects. For the simulations, the Robot Operating System (ROS), the global coordinate system is used.…”
Section: Simulation Resultsmentioning
confidence: 95%
“…A dedicated software program utilizes trigonometrical relations among the markers in captured images and the locations of the cameras to calculate the positions and orientations of the body joints. Many studies confirmed the excellent positioning performance of these motion capture systems in both static and dynamic tests [95]- [97]. As a result, optical tracking systems are regarded as the gold standard for verifying tracking reliability of other motion sensors [76], [98]- [100].…”
Section: Optical Motion Tracking Systemsmentioning
confidence: 98%
“…In general, feature engineering involves feature extraction and feature selection. In many related works, feature engineering is performed manually based on authors' understanding of human movements [33]- [37], [54], [97], [98], [126], [127]. For example, in [34], underarm angles and Euclidean distance between the elbows were used to describe the lifting of the arms.…”
Section: Feature Engineeringmentioning
confidence: 99%
See 1 more Smart Citation